2021
DOI: 10.1007/s00167-021-06610-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ankle instability has no correlation with the number of ruptured ligaments in severe anterolateral sprain: a systematic review and meta-analysis

Abstract: Purpose Despite being a signiicant public health problem, ankle sprains' prognostic factors are largely unknown. This review aimed to systematically analyze the literature on acute ankle sprains to compare the prognosis of a combined anterior taloibular (ATFL) and calcaneoibular (CFL) ligaments rupture with an isolated ATFL rupture in terms of progression to chronic ankle instability and other clinical outcomes. Methods The databases for Pubmed, CENTRAL and Web of Science were searched. Clinical studies report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that the development of CAI has no correlation with the severity of ATFL/CFL injuries as assessed by clinical tests after LAS. 39 Thus, the initial severity of injury to proprioceptive nerves within the sprained ligaments might not be a determinant for ankle proprioception deficiency in CAI.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported that the development of CAI has no correlation with the severity of ATFL/CFL injuries as assessed by clinical tests after LAS. 39 Thus, the initial severity of injury to proprioceptive nerves within the sprained ligaments might not be a determinant for ankle proprioception deficiency in CAI.…”
Section: Discussionmentioning
confidence: 98%
“…[ 31 ] and Pacheco et al. [ 32 ] regarding prognostic factors associated with poor clinical outcomes in individuals with ankle injuries. Both studies listed injury severity as a clinical indicator for poor prognosis, but also determined that there is insufficient evidence at this point to offer any recommendations about clinical traits that would prognosticate a poor recovery or progressing disability.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies listed injury severity as a clinical indicator for poor prognosis, but also determined that there is insufficient evidence at this point to offer any recommendations about clinical traits that would prognosticate a poor recovery or progressing disability. Further research is needed to accurately understand the prognosis and potential consequences of ankle sprains [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ankle sprains are the most common cause of ATFL injuries. If not treated promptly and properly after injury, repeated ATFL damage may result in chronic lateral ankle instability (CLAI) ( Pacheco et al, 2021 ). Therefore, appropriate treatment should be performed promptly to reduce the long-term complications of ATFL injuries.…”
Section: Introductionmentioning
confidence: 99%